Systematic Literatur Riview: Strategi Penguatan Kualitas Agen Untuk Memajukan Pangsa Pasar Asuransi Umum Di Indonesia - Sidik, syahrial; Wahyuari, Wahyuari; Nasyubun, M. (Community Engagement and Emergence Journal (CEEJ), 2026)
The general insurance industry in Indonesia faces the challenge of low market penetration (below 4%) due to minimal risk literacy and public trust. Insurance agents play a central role as educators and bridges of trust, but strategies to strengthen their position in emerging markets have not been explored holistically. This study aims to formulate strategies to strengthen agent quality in order to advance market share through a Systematic Literature Review (SLR) method using the TCCM (Theory, Context, Characteristics, Methodology) framework. Using the PRISMA 2020 protocol, this study selected 1,000 articles from the Google Scholar and Emerald Insight databases (2016–2026), resulting in 30 relevant final articles. The analysis results show a surge in post-pandemic research interest and a dominance of studies from emerging market contexts that emphasize the “Phygital” (Physical + Digital) approach. This study proposes the “Hybrid-Trusted Agent” model, which integrates digital competence, ethical behavior, and technical expertise as key determinants of market performance. In conclusion, the transformation from transactional sales to relationship marketing is essential to improve customer retention and sustainable market growth.